Research on new immunomodulators from marine animals - Pusset, Jacques (Malaysian Journal of Science, 2000)
A review on the mechanism of action of Rapamycine and FK-506 and the discovery of bistramide, an immunosuppressive compound from Lissoclinum bistratum, were discussed. ABSTRAK Satu tinjauan mengenai mekanisma tindakan Rapamisina dan FK-506 dan penemuan bistramida sebatian yang memaparkan aktiviti perencat imun, dibincangkan. (Immunomodulators, Lissoclinum bistratum, therapeutic agent, bistramide A, agelastatin A)